The Hero In The Pre-Islamic Poetic Consciousness - Ahmad , Adnan; Nassour , Azdasher (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The poetic consciousness of the pre-Islamic period is full of various images of the "hero" whose heroship exceeds the idea of chivalry further up to an extensive richness denoted by the the lexicon of "heroicism", as well as by the poetic capturing of the heroic acts. Thus, a heroic poetry has emerged to be an example followed by many poets later to assimilate those heroic values. Generally speaking, the poet of the pre-islamic period is one of the tribe heroes adapting values of heroship which have always characterised the pre islamic community. Accordingly, the concept of the " war hero" has formed the the poetic consciousness in terms of bravery and strength. So well does the "peace hero" as having been the social hero representing the values of genorosity, good neighbor, and helping the needy. There are also many other values which can’t be separated in many poems, especially when connected with collective pride that is often represented by heroes carrying the tribal fanaticism.